PENGARUH KOMPENSASI DAN PENGAWASAN TERHADAP KINERJA GURU ASN MELALUI MOTIVASI KERJA PADA SMKN 1 SITUBONDO - VERY SUKARELA (Al-Fikru : Jurnal Pendidikan Dan Sains, 2020)
The teacher is one of the educational staff who has a role as one of the determining factors for the success of educational goals, because the teacher is in direct contact with students, to provide guidance that will produce the expected graduate. Teachers are human resources who are planners, actors and determinants of achieving organizational goals. The teacher is the backbone in educational activities especially those related to teaching and learning activities, without the teacher's role the teaching and learning process will be disrupted or even failed. Therefore in the management of education the role of teachers must always be improved in order to produce quality human resources who are able to compete in the global era. The objectives of this study are: i) Determine the effect of compensation on work motivation; ii) Knowing the effect of supervision on work motivation; iii) Determine the effect of compensation on ASN performance; iv) Knowing the effect of supervision on ASN performance v) Knowing the effect of work motivation on ASN performance; vi) Determine the effect of compensation on ASN performance through work motivation; vii) Determine the effect of supervision on ASN performance through work motivation. This research is a quantitative study using a Likert scale. The sample used was the entire population of 32 certified ASN teachers. The statistical analysis used is path analysis, using SPSS 17. The results showed that: (i) Compensation did not significantly influence work motivation; (ii) Supervision has a significant effect on work motivation; (iii) Compensation has no significant effect on ASN performance; (iv) Supervision has a significant effect on ASN performance; (v) Work Motivation has a significant effect on ASN performance; (vi) Compensation does not significantly influence ASN performance through work motivation; (vii) Supervision has a significant effect on ASN performance through work motivation. Keyword: Likert scale, Path analysis